2021
DOI: 10.1016/j.burnso.2021.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of burn injury during COVID-19 pandemic in Tokyo: A descriptive study

Abstract: Introduction Coronavirus disease 2019 (COVID-19) has drastically changed everyday life worldwide. This study aimed to determine how COVID-19 affected the characteristics and outcomes of patients with severe burn injury by examining a city-wide burn database in Tokyo. Patients and Methods A descriptive study was conducted in 14 burn centers using the Tokyo Burn Unit Association registry from 1999–2020. The pandemic started in 2020, while the stay-at-home order lasted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
4
9
0
Order By: Relevance
“…Similar studies were published by other burn centres from economically developed countries, such as the UK, the US, Canada, and Japan [ 5 , 10 , 11 , 12 , 13 ]. D'Asta et al reported a decrease in adult burn patients by 60% during the lockdown, although the number of paediatric burn cases increased by 8% at the same time [11] .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Similar studies were published by other burn centres from economically developed countries, such as the UK, the US, Canada, and Japan [ 5 , 10 , 11 , 12 , 13 ]. D'Asta et al reported a decrease in adult burn patients by 60% during the lockdown, although the number of paediatric burn cases increased by 8% at the same time [11] .…”
Section: Discussionsupporting
confidence: 78%
“…This might be explained by the fact that the lockdown policies mainly affected the retail, culture, and gastronomy sectors and spared the heavy industry where hygiene concepts or short-time working was introduced early in Germany. No relationship could be identified in previously published studies, which may be explained by the generally lower incidence of work-related burn injuries [ 5 , 18 ]. Further, we expected a rise in burn patients with concomitant SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some burn units have reported their measures [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], there are no data on the impact of these with regard to treatment outcomes. Most of the data published in the literature thus far refer to epidemiological and demographic data in addition to injury and treatment characteristics of burn patients [ 8 , 15 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sporadic COVID-19 cases were noted in Japan in January 2020. The governor of Tokyo Metropolis announced the first stay-at-home order in April 2020, which lasted one month, then the second in January 2021 [ 14 ]. There were three surges of newly diagnosed COVID-19 cases during the study period.…”
Section: Methodsmentioning
confidence: 99%